Reinforced concrete building design project: project based learning (case study) / Muhammad Iman Hakim Mohd Fazly - Mohd Fazly, Muhammad Iman Hakim (2022)
Design work is not an easy job and should not be underestimated by any civil engineer because incorrect calculations can result in unfavorable outcomes for the building we design. So, after receiving knowledge about design work from my lecturer, Sir Ahmad Idzwan, l gained a better understanding of design work as well as the proper and correct calculation for each structure element in each house construction. Furthermore, I can determine the effect of the effect if a situation such as this is lacking, as well as what will be in the design work. Design work is critical in any construction project, whether it's a house, apartment, or retail space, because it allows us as civil engineers to determine the maximum capacity of the structure in order to prevent it from collapsing while serving the community. Later on, I was able to learn about some of the appendices used in actual construction in Malaysia, such as Eurocode and British Standard, thanks to this design work.